2008
DOI: 10.1029/2007wr006353
|View full text |Cite
|
Sign up to set email alerts
|

An exact solution for ideal dam‐break floods on steep slopes

Abstract: [1] The shallow-water equations are used to model the flow resulting from the sudden release of a finite volume of frictionless, incompressible fluid down a uniform slope of arbitrary inclination. The hodograph transformation and Riemann's method make it possible to transform the governing equations into a linear system and then deduce an exact analytical solution expressed in terms of readily evaluated integrals. Although the solution treats an idealized case never strictly realized in nature, it is uniquely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 37 publications
2
37
0
1
Order By: Relevance
“…This contrasts somehow with what we know of inertial flows. For inviscid fluids instantaneously released on a dry horizontal plane, dam-break theory predicts that the front velocity u f does not vary with time, but solely with the initial flow depth h 0 : u f = 2gh 0 (Ritter's solution); for sloping beds, the front is continuously accelerating [54]. If we take the example of Fig.…”
Section: Front Position Contact Line and Flow-depth Profilementioning
confidence: 99%
“…This contrasts somehow with what we know of inertial flows. For inviscid fluids instantaneously released on a dry horizontal plane, dam-break theory predicts that the front velocity u f does not vary with time, but solely with the initial flow depth h 0 : u f = 2gh 0 (Ritter's solution); for sloping beds, the front is continuously accelerating [54]. If we take the example of Fig.…”
Section: Front Position Contact Line and Flow-depth Profilementioning
confidence: 99%
“…Simulaciones numéricas con ecuaciones 2D conocidas como shallow water equations (SWE) fueron realizadas por (Fraccarollo y Toro, 1995;Frazão y Zech, 2002). Otros ejemplos en los cuales también se obtuvo una representación adecuada usando modelos 2D fueron presentados por Aricò et al (2007) y Ancey et al (2008). Los modelos numéricos tratados hasta el momento suponen velocidades y aceleraciones verticales despreciables lo que da lugar a una distribución hidrostática de presiones.…”
Section: Introductionunclassified
“…More recently Mangeney et al [15] found a solution for the 1D sloped Dam-Break with friction using the Method of characteristics and applied it to avalanches. Ancey et al [16] presented a solution for steep slopes.…”
Section: Sve Analytical Solutionsmentioning
confidence: 99%
“…The next step is finding the solution for Area 3 variables. The characteristics (16) and (18) are the solution for the ordinary differential equations (12) and (13) as long as relations (15) and (17) are satisfied. In Area 3 along the negative characteristic (18) we have:…”
Section: Step 2 -Dam-breakmentioning
confidence: 99%